Synthesis and properties of new carbosilane copolymers and symmetrical bis(alkoxybenzylidene)- 1,5-naphthalene dimers based on bisphenol schiff base monomers / Wisam Naji Atiyah Al-Mehana - Wisam Naji Atiyah, Al-Mehana (2015)

(untitled)
A series of new carbosilane bisphenol azine copolymers with different substituted groups (electron-donating and/or withdrawing) (Pa1-Pa6) were successfully synthesized by polycondensation reaction using bis(chloromethyl) dimethylsilane. The number-average molecular weights of the copolymers were between 2322 and 9805, and the polydispersity index between 1.04 and 2.10. The monomers showed good solubility in DMSO and DMF except for a5 and a6 which required high temperature to dissolve and the copolymers exhibited excellent solubility in common organic solvents (THF, CHCl3 and DMF) but insoluble in hydroxyl-group containing solvents (CH3OH and C2H5OH). All the copolymers showed good thermal stabilities with their temperatures at 10% weight loss being higher than 265.96°C under nitrogen. The copolymers exhibited strong UV-vis absorptions in dilute DMF with λmax at 318-351 nm and photoluminescence results showed a medium photoluminescence in the blue region with λmax at 416-422 nm. From cyclic voltammetry (CV) measurements the electrochemical band gaps (Eg) calculated were below 2.00 eV. The influence of the substitution groups on the molecular weight and all the physical properties was studied. After successfully synthesized the new polycarbosilanes based on the full conjugated bisphenol azine monomers, newly higher conjugation of polycarbosilanes were synthesised (Pb1-Pb7) based on 1,4-phenylene and 1,5-naphthalene bis-Schiff base. The number-average molecular weights of the copolymers were between 2401 and 7414, and the polydispersity index between 1.21 and 2.04. The copolymers exhibited vi excellent solubility in common organic solvents (THF, CHCl3 and DMF) and partially dissolving in hydroxyl-group containing solvents (CH3OH and C2H5OH). All the copolymers showed higher thermal stabilities compared to the carbosilane copolymers containing azines with their temperatures at 10% weight loss being higher than 324°C under nitrogen. The copolymers exhibited strong UV-vis absorptions in dilute DMF, where the copolymers containing 1,4-phenylene appeared as two peaks at λmax 287-365 nm and the copolymers containing 1,5-naphthalene appeared as three peaks at λmax 273- 363 nm. Photoluminescent results showed a medium photoluminescence in the blue region with λmax at 416-429 nm. The HOMO and LUMO were investigated for these copolymers to estimate the band gaps. In addition, two new series of homologous symmetrical dimers N,N-bis(4-alkoxy- benzylidene)-1,5-naphthalenediimine grouped as series (c) and N,N-bis (3-methoxy-4-alkoxy- benzylidene)-1,5-naphthalenediimine grouped as series (d) with different lengths of terminal alkyl groups of even parity ranging from butyl to octadecyl were synthesized and characterized. The mesomorphic properties of these compounds were investigated via differential scanning calorimetry and optical polarizing microscopy. A diversed phase-transition behavior was observed for the members of series (c) which could be attributed to the possible molecular conformations. Compounds with chain length in a range of C6H13 to C12H33 showed smectic C phase while C14H29 and C16H33 displayed smectic and nematic phase. The dimers containing butyl and octadecyl moiety did not display mesogenic properties. Meanwhile, series (d) did not exhibit any liquid crystalline phase due to the effect of vii methoxy group on molecule. All of the compounds in the first series (c1-c8) have high thermal stability and did not show significant decomposition below 400ºC in nitrogen atmosphere. UV-Vis results showed strong peak at 281-283 nm and weak peak at 362– 363 nm and fluorescent peak of the resultant compound was in the red region at 516- 518 nm. The chemical structures of synthesized compounds were confirmed by FT-IR, 1H, 13C NMR, 2D NMR and X-Ray crystallography.